Performance and emission characteristics of a spark ignition engine fuelled with butanol isomer-gasoline blends. (December 2017) - Yusoff, M.N.A.M.; Zulkifli, N.W.M.; Masjuki, H.H.; Harith, M.H.; Syahir, A.Z.; Kalam, M.A.; Mansor, M.F.; Azham, A.; Khuong, L.S.
Highlights: Blends containing 20 vol% of butanol isomers in gasoline were tested on SI engine. T, BP, BSFC, BTE and CO emissions are higher for butanol isomer-gasoline blends. iBu20 and nBu20 gives the lowest CO and HC emissions, respectively. Butanol isomer-gasoline blends give lower NO emissions except for iBu20. iBu20 gives the best engine performance and emissions among all tested blends. Abstract: The heavy reliance on petroleum-derived fuels such as gasoline in the transportation sector is one of the major causes of environmental pollution. For this reason, there is a critical need to develop cleaner alternative fuels. Butanol is an alcohol with four different isomers that can be blended with gasoline to produce cleaner alternative fuels because of their favourable physicochemical properties compared to ethanol. This study examined the effect of butanol isomer-gasoline blends on the performance and emission characteristics of a spark ignition engine. The butanol isomers; n -butanol, sec -butanol, tert -butanol and isobutanol are mixed with pure gasoline at a volume fraction of 20 vol%, and the physicochemical properties of these blends are measured. Tests are conducted on a SI engine at full throttle condition within an engine speed range of 1000–5000 rpm. The results show that there is a significant increase in the engine torque, brake power, brake specific fuel consumption and CO2 emissions with respect to those for pure gasoline. The butanol isomers-gasoline blends give slightly higher brake thermal efficiency and exhaust gas temperature than pure gasoline at higher engine speeds. The iBu20 blend (20 vol% of isobutanol in gasoline) gives the highest engine torque, brake power and brake thermal efficiency among all of the blends tested in this study. The isobutanol and n -butanol blend results in the lowest CO and HC emissions, respectively. In addition, all of the butanol isomer-gasoline blends yield lower NO emissions except for the isobutanol-gasoline blend.